Strength and ductility of RC jacketed columns: A simplified analytical method. (1st September 2016) - Minafò, Giovanni; Di Trapani, Fabio; Amato, Giuseppina
Highlights: Square RC jacketed sections subjected to axial load and bending moment are considered. A simplified method for calculating moment–curvature curves is proposed. Comparisons are made with numerical analyses and experimental results. A procedure is derived for ductility analysis and ductility-assigned design. Abstract: Reinforced concrete (RC) jacketing is a common method for retrofitting existing columns with poor structural performance. It can be applied in two different ways: if the continuity of the jacket is ensured, the axial load of the column can be transferred to the jacket, which will be directly loaded; conversely, if no continuity is provided, the jacket will induce only confinement action. In both cases the strength and ductility evaluation is rather complex, due to the different physical phenomena included, such as confinement, core–jacket composite action, preload and buckling of longitudinal bars. Although different theoretical studies have been carried out to calculate the confinement effects, a practical approach to evaluate the flexural capacity and ductility is still missing. The calculation of these quantities is often related to the use of commercial software, taking advantage of numerical methods such as fibre method or finite element method. This paper presents a simplified approach to calculate the flexural strength and ductility of square RC jacketed sections subjected to axial load and bending moment. In particular the proposed approach is based on the calibration of the stress-block parameters including the confinement effect. Equilibrium equations are determined and buckling of longitudinal bars is modelled with a suitable stress–strain law. Moment–curvature curves are derived with simple calculations. Finally, comparisons are made with numerical analyses carried out with the code OpenSees and with experimental data available in the literature, showing good agreement.